Current Status of Bibliometrics-Based Research on Measurement and Communication Technology for Space Tracking Ships - Haoyu Jiang; Yunsheng Ma; Shengqing Zeng; Yutao Tian; Dapeng Zhang (Journal of Marine Science and Engineering, 2025)
Space tracking ships are critical assets in modern space exploration, overcoming the limitations of land-based tracking systems by providing real-time telemetry, trajectory monitoring, and communication support for satellites and spacecraft. However, the existing literature offers limited insights into the historical development, technological evolution, and collaborative research trends of these specialized vessels. This study employs a bibliometric analysis using CiteSpace (6.3.R1) to identify research trends, highlight key technological advancements, and assess international collaboration. By analyzing publications from major contributors, including the United States, the former Soviet Union, France, and China, the paper reveals technological innovations such as advancements in measurement systems, communication technologies, and the integration of artificial intelligence (AI) for enhanced tracking precision. Structural and operational analyses emphasize the importance of design factors, including ship dimensions and internal systems, for ensuring optimal performance in challenging maritime environments. The findings highlight evolving technological priorities and persistent gaps in international collaboration, suggesting opportunities for global partnerships to advance the field. This study bridges historical and technical gaps, providing valuable insights for enhancing the efficiency and strategic relevance of space tracking ships in future space exploration missions.